PENGARUH WORK LIFE BALANCE DAN BUDAYA ORGANISASI TERHADAP EMPLOYEE ENGAGEMENT PAD GENERASI MILENIAL DI PT. GUNUNG SAWIT MAS DESA RANTAU PANJANG KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU - Ahmad Fauzi Batu Bara; Arrafiqur Rahman (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2020)
This study aims to determine the effect of work life balance and organizational culture on employee engagement in the millennial generation of PT. Gunug Sawit Mas, Rantau Panjang Village, Tambusai District, Rokan Hulu Regency. The population in this study is the millennial generation employees of PT. Gunug Sawit Mas, Rantau Panjang Village, Tambusai District, Rokan Hulu Regency. The study sample used a saturated or census sampling technique, with a total of 80 people. Data collection techniques using the method of observation, questionnaire methods, interviews and documentation. Data analysis using multiple linear regression with the help of the SPSS program. From the partial test results obtained the value of t count work life balance of 28,498, and t count of organizational culture 57,609. The conclusion of this research is based on partial test or simultaneously work life balance and organizational culture have a significant effect on employee engagement. The magnitude of the effect shown is 98.1%, while the rest is 1.9% employee engagement explained by other variables not examined in this study or other causes outside the model.